Rapid and Scalable Plant-Based Production of a Potent Plasmin Inhibitor Peptide - Jackson, Mark A.; Yap, Kuok; Poth, Aaron G.; Gilding, Edward K.; Swedberg, Joakim E.; Poon, Simon; Qu, Haiou; Durek, Thomas; Harris, Karen; Anderson, Marilyn A.; Craik, David J. (Frontiers in Plant Science, 2019)
The backbone cyclic and disulfide bridged sunflower trypsin inhibitor (SFTI-1) peptide is a proven effective scaffold for a range of peptide therapeutics. For production at laboratory scale, solid phase peptide synthesis techniques are widely used, but these synthetic approaches are costly and environmentally taxing at large scale. Here we developed a plant-based approach for the recombinant production of SFTI-1 based peptide drugs. We show that transient expression in Nicotiana benthamiana allows for rapid peptide production, provided that asparaginyl endopeptidase enzymes with peptide-ligase functionality are co-expressed with the substrate peptide gene. Without co-expression, no target cyclic peptides are detected, reflecting rapid in planta degradation of non-cyclized substrate. We test this recombinant production system by expressing a SFTI-1 based therapeutic candidate that displays potent and selective inhibition of human plasmin. By using an innovative multi-unit peptide expression cassette we show that in planta yields reach ~60 g/g dry weight at 6 days post leaf infiltration. Using nuclear magnetic resonance structural analysis and functional in vitro assays, we demonstrate the equivalence of plant and synthetically derived plasmin inhibitor peptide. The methods and insights gained in this study provide opportunities for the large scale, cost effective production of SFTI-1 based therapeutics.